Community Awareness for Screening Non-Communicable Diseases - Prihanti, Gita Sekar; Wilyani, Dwi; Isnaini, Faradila; Ailani, Achmad Fauzan; Humaira, Azkia Akbari; Kurniawan, Iga Karisma; Rahayu, Kartika Puji; Hadiyanti, Lisa Aprilia; Santoso, Shabrina Rahma (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
Non-Communicable Diseases (NCD), also known as chronic diseases such as hypertension, diabetes, and obesity, are from combined genetic, physiological, environmental, and behavioral factors. The number of NCD screening visits at Ngletih Public Health Center (PHC) Kediri decreased in 2018 was 29% and became 24% in 2019, with a target of 10,718 people. This study aimed to know the factors affecting community awareness for screening NCD. The respondents are people aged 15-59 years who live in the working area of Ngletih PHC and have never been diagnosed with hypertension, diabetes, and obesity. This research used an analytical observational study with a cross-sectional design. The number of samples taken is 1,000 with purposive sampling; then, respondents filled out 27 questionnaires self-administered. The data analysis was implemented univariate, bivariate using chi-square, and multivariate using multiple logistic regression. The chi-square test showed eight variables that increase awareness for screening NCD: age, gender, education level, marital status, family history, source of health information, knowledge, and attitude. The multiple logistic regression tests showed five factors that increase awareness for screening NCD: age, gender, marital status, sources of health information, and knowledge. The dominant factor affecting community awareness for screening NCD is a source of health information (p=0.023; OR=4.353; CI=1.220-15.537).